PEMBENTUKAN KELOMPOK ASUHAN MANDIRI TAMAN OBAT KELUARGA (TOGA) JATI HUSADA MULYA DAN PENGARUHNYA DALAM MENINGKATKAN KEMAMPUAN SWAMEDIKASI PENYAKIT COMMON COLD DI DUSUN WATU ARGOMULYO SEDAYU BANTUL - Anis Oki Tyassetya; Trilestari; Nurul Kusumawardani (Bajang Institute, 2021)
The common cold is one type of infectious disease that often appears in the community. At the Sedayu I Health Center the common cold was always in the top 10 disease. However, this phenomenon is not supported by the availability of drugs. Therefore, the use of herbal medicine can be an alternative. While only a few people in Argomulyo know about medicinal plants. Therefore, it is necessary to form the Asman TOGA group for increasing the ability to self medication for common cold disease. The subjects on the service are the community group of the hamlet of Watu Argomulyo Sedayu Bantul, totaling 33 people. The activity was carried out in June-August 2019 and was divided into 4 stages : preparation, implementation, monitoring and evaluation. This community service program has succeeded in increasing self medication capabilities for common cold disease and has also increased the utilization and ownership of TOGA.